2007
DOI: 10.1177/008124630703700310
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Religious Orientation and Pressure in Psychology I Students at the University of the Witwatersrand

Abstract: This study considers the relationship between religious orientation and pressure in 494 first-year Psychology students at the University of the Witwatersrand, South Africa. Religious orientation is defined according to Allport's concepts of intrinsic and extrinsic religious orientation and was measured using the Allport-Ross Religious Orientation Scale-Revised. Pressure is a concept used by Weiten to define the everyday life stress experienced by individuals and was measured in this study using Weiten's Pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Individuals with mature faith and internalized religious teachings tend to be better able to accept the conditions they face (Ashby & Huffman, 1999), because they are less likely to be stimulated by impulses or incentives and fear of their surroundings (Allport, 1950). They are more capable of resisting pressure from the surrounding as well (Laher, 2007). Hence, even though they live in the collective society, participants in this study are not tempted to set a high standard that cannot be achieved to satisfy their surroundings.…”
Section: Discussionmentioning
confidence: 95%
“…Individuals with mature faith and internalized religious teachings tend to be better able to accept the conditions they face (Ashby & Huffman, 1999), because they are less likely to be stimulated by impulses or incentives and fear of their surroundings (Allport, 1950). They are more capable of resisting pressure from the surrounding as well (Laher, 2007). Hence, even though they live in the collective society, participants in this study are not tempted to set a high standard that cannot be achieved to satisfy their surroundings.…”
Section: Discussionmentioning
confidence: 95%
“…As religious orientation examines the motives of individuals to pursue their religious beliefs; their religious approach can be classified as intrinsic or extrinsic (Allport and Ross, 1967;Noble et al, 2007). Where intrinsic individuals are those who consider religion as their life's purpose, they have strong commitment towards their religion's doctrines and beliefs and their behaviour centres around religious principles and values (Laher, 2007;Noble et al, 2007;Mansori et al, 2015); for extrinsic individuals' religion is not their central reason and does not govern their motives (Allport and Ross, 1967;Laher, 2007;Meagher, 2018). Furthermore, Ajzen's theory predicts human behaviour.…”
Section: Religious Knowledge and Actual Purchase Behaviourmentioning
confidence: 99%
“…This research revealed that religious orientation had a positive impact on the loyalty of viewers. Specifically, both intrinsic and extrinsic religious measures are seen as important explanatory instruments of people's behavior (Donahue, 1985;Laher, 2007). Religion rules and norms could also form the customers' tastes and preferences (Assadi, 2003).…”
Section: Religious Orientationmentioning
confidence: 99%